Establishment and application of a method of tagged-amplicon deep sequencing for low-abundance drug resistance in HIV-1 - Li, Yang; Han, Leilei; Wang, Yanglan; Wang, Xiaolin; Jia, Lei; Li, Jingyun; Han, Jingwan; Zhao, Jin; Li, Hanping; Li, Lin (Frontiers in Microbiology, 2022)
In the latest HIV-1 global drug resistance report released by WHO, countries are advised to strengthen pre-treatment monitoring of drug resistance in AIDS patients. In this study, we established an NGS-based segmented amplification HIV-1 drug resistance mutation detection method. The pol region of HIV-1 was divided into three short fragments for NGS. The entire amplification and sequencing panel were more cost-effective and batched by using the barcode sequence corresponding to the sample. Each parameter was evaluated using samples with known resistance variants frequencies. The nucleotide sequence error rate, amino acid error rate and noise value of the NGS-based segmented amplification method were both less than 1%. When the threshold was 2%, the consensus sequences of the HIV-1 NL4-3 strain was completely consistent with the Sanger sequences. This method can detect the minimum viral load of the sample at 102 copies/ml, and the input frequency and detection frequency of HIV-1 resistance mutations within the range of 1%-100% had good conformity (R2=0.9963; R2=0.9955). This method had no non-specific amplification for Hepatitis B and C. Under the 2% threshold, the incidence of surveillance drug resistance mutations in ART-naive HIV-infected patients was 20.69%, among which NRTIs class resistance mutations were mainly.